Psychosocial, Demographic, and Illness‐Related Factors Associated With Acute Traumatic Stress Responses in Parents of Children With a Serious Illness or Injury. Issue 3 (23rd June 2017) - Muscara, Frank; McCarthy, Maria C.; Thompson, Emma J.; Heaney, Claire‐Marie; Hearps, Stephen J. C.; Rayner, Meredith; Burke, Kylie; Nicholson, Jan M.; Anderson, Vicki A.
Abstract : This study investigated factors associated with acute stress symptoms in parents of seriously ill children across a range of illnesses and treatment settings within a pediatric hospital setting. It was hypothesized that psychosocial variables would be more strongly associated with acute stress responses than demographic and child illness variables. Participants were 115 mothers and 56 fathers of children treated within the oncology, cardiology, and intensive care departments of a pediatric hospital. Acute stress, psychosocial, demographic, and medical data were collected within the first 4 weeks of the child's hospital admission. A robust hierarchical regression model revealed that psychosocial factors significantly explained 36.8% of the variance in parent acute stress responses ( p < .001); demographic variables significantly added a further 4.5% ( p = .022), but illness‐related factors did not contribute to the model. Findings support the implementation of a general psychosocial screening approach for parents across the wider hospital system, and that psychosocial risk factors may be targeted in interventions across different illnesses and treatment settings to improve parent outcomes.